HẠT VẬT LIỆU CHẾ TẠO TỪ BÙN ĐỎ BAUXIT BẢO LỘC VÀ ĐỊNH HƯỚNG ỨNG DỤNG TRONG XỬ LÝ Ô NHIỄM NƯỚC THẢI - Minh, Nguyễn Trung (Vietnam Journal of Earth Sciences, 2011)
Applications of modified granular red mud of refining Bao Loc bauxite for waste water treatmentRed mud is a solid waste product of exploiting and refining bauxite. There were many of researches of Red mud in order to remove a part or a whole by using useful components as well. Bao Loc red mud is a solid waste product of exploiting Bao Loc - Tay Nguyen bauxite. Studying of developing the products derived from red mud plays an important and urgent role to satisfy two current proposes: (1) To reduce the waste products of the exploiting and refining processbauxite; (2) To take advantage of redundant waste products of the exploiting process in order to produce new materialswhich can be used for treating heavy metals as well as other poisons in the environment. It is the real and pressing requirement in developed economic area of Tay Nguyen and many of other provinces such as Ha Giang, Cao Bang, Lang Son and the coastal zone of central region.In this research, we have carried out the plan of taking advantage of useful components from red mud to produce a new material being of treating heavy metals ability and eco-friendly properties for developing stably. In addition, it also has a good ability of adsorbing with low cost and suitable to Vietnam climate. The initial results of heavy metals (Cu, Pb, Zn, Cd, Cr, As) adsorbing as well as the chemical, physical, isothermal absorbing parameters indicate the ability of using red mud in waste water treatment. In this paper, the detailed result of treating Pb ion has been shown. Red mud was mixed with some kinds of additive materials (as carbon, kaolin, liquid glass Na2SiO3) in appropriate ratios before adding amount of suitable water and burned.The adsorption capacity (Qe) of material BVNQ for ion Pb2+ is 21.7 (mg/g) and reach to the number 68.73% to remove Pb. It can be chosen for waste water treatment technology.